2021
DOI: 10.3389/fpls.2021.629859
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of Banana Leaf Blight Pathogen Fusarium sacchari str. FS66 Harbors Widespread Gene Transfer From Fusarium oxysporum

Abstract: Fusarium species have been identified as pathogens causing many different plant diseases, and here we report an emerging banana leaf blight (BLB) caused by F. sacchari (Fs) discovered in Guangdong, China. From the symptomatic tissues collected in the field, a fungal isolate was obtained, which induced similar symptoms on healthy banana seedlings after inoculation. Koch’s postulates were fulfilled after the re-isolation of the pathogen. Phylogenetic analysis on two gene segments and the whole genome sequence id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…The SIX genes play a role in the pathogenicity of Fusarium wilt; SIX1, SIX2, SIX6, SIX7, SIX9G1, SIX11, and SIX13 were detected in the FFSC species [34,37]. The present study showed that the F. mindanaoense genome possessed the SIX6 gene exclusively, which matched with those of the FFSC with low e-values (Table 2; 0-3.92 × 10 −125 ).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The SIX genes play a role in the pathogenicity of Fusarium wilt; SIX1, SIX2, SIX6, SIX7, SIX9G1, SIX11, and SIX13 were detected in the FFSC species [34,37]. The present study showed that the F. mindanaoense genome possessed the SIX6 gene exclusively, which matched with those of the FFSC with low e-values (Table 2; 0-3.92 × 10 −125 ).…”
Section: Discussionsupporting
confidence: 51%
“…), and F. musae (fruit rot on Musa sp.) belonging to FFSC were reported as banana pathogens [34][35][36][37][38][39][40][41]. These species do not cause Fusarium wilt of bananas.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Fusarium comprises the most important and notorious fungi, consisting of diverse species of complex and economically destructive phytopathogens associated with leaf-blight diseases on a wide range of host plants, for example, banana leaf-blight disease, peanut leaf blight, and plum leaf blight [ 40 , 41 , 42 ]. Some Dendrobium plants have been reported as disease hosts caused by Fusarium spp., for example, dieback disease [ 43 ] and soft rot disease of D. officinale in China [ 44 ] and leaf blotch of D. antennatum in Malaysia [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extreme weather events and pathogens have compromised banana harvests in China. For example, typhoon Mangkhut ravaged banana crops in Guangdong in 2018, and Fusarium Sacchari (a fungal plant pathogen affecting banana leaves) was also discovered in the province in 2016 (Cui et al 2021). The resources available to farmers via agricultural cooperatives can help them learn new adaptation and mitigation strategies to cope with such adversities.…”
Section: Introductionmentioning
confidence: 99%